Literature Review: Burnout pada Perawat di Rumah Sakit Swasta - Andreas Klemens Wienanda; Harry; Muhammad Rezki Zanuar; Namira Amanda G; Natasya Luila Sissarian; Vip Paramarta (Bulletin of Community Engagement, 2024)
Burnout is a major problem for private hospital nurses, impacting their mental health and the quality of healthcare. This phenomenon is characterized by a sense of emotional exhaustion, loss of personal sense, and decreased levels of personal achievement. The purpose of this study was to provide an overview of burnout, find its causes, and make recommendations on how to overcome burnout in private hospitals. The data shows that high workload, lack of managerial support, and unsupportive work environment are the main factors that cause about 35% to 54% of nurses to experience burnout symptoms. Nurse burnout impacts both patients and nurses as a whole. Consequently, to solve this problem, a comprehensive approach is required.